Greg's Environment Factors To Be A Favorite Student In Thor Freudenthal's Diary Of A Wimpy Kid Movie (2010): A Behaviorist Approach - Peruanti, Dessy, Dr. Phil Dewi Candraningrum, S.Pd., M.Ed, Siti Fatimah, S.Pd., M.Hum (2013)
The major problem in this research paper is to describe how Greg's environment factors to be a favorite student reflected in Thor Freudenthal's Diary of a Wimpy Kid movie (2010) are. The purposes of this research paper are to analyze Greg's environment factors to be a favorite student in Thor Freudenthal's Diary of a Wimpy Kid movie (2010) based on the structural element of the movie and based on the behaviorist approach. The object study is Diary of a Wimpy Kid movie (2010) by Thor Freudenthal. It is used in behaviorist approach. In analyzing this study, the researcher uses qualitative research and behaviorist approach. The primary data source of this research is Diary of a Wimpy Kid movie (2010) by Thor Freudenthal and produced by 20th Century Fox Pictures. The secondary data sources are books and the other sources that support the analysis. Having analyzed this research paper, the researcher presents two conclusions. First, Diary of a Wimpy Kid movie is a live action movie produced in 2010 and directed by Thor Freudenthal. All of the structural elements of the movie have the best connection to each other. This movie is suitable to be watched by all ages, because best friend is part of a person's life. Second, the issue of this research paper is reflected in all behaviorist aspects. Greg's environment factors to be a favorite student, like from family, peers, school or education, and society or community. The big influence of environment factors come from school or educational environment by the existence of rotten cheese and from the society or community environment, namely the naughty boys. Greg is to be a favorite student, even is not thought by him before and he is listed in his middle school's yearbook as the cutest friend category with Rowley.